Ms. marvel: the new mutant (2023) ebook - Vellani, Iman (Ms. Marvel: The New Mutant, 2024)
Collects Ms. Marvel: The New Mutant (2023) #1-4, material from All-New Marvel Now! Point One (2014) #1. Kamala Khan is back - and she's an X-Man! Ms. Marvel bursts into the next phase of her life in an exciting adventure co-written by Iman Vellani, the MCU's own Kamala, and Sabir Pirzada of both DARK WEB: MS. MARVEL and her Disney+ series! That's right - the good news is that in the wake of her recent world-saving sacrifice, Ms. Marvel has been resurrected via Krakoan technology! What a way to learn she's both an Inhuman AND a mutant! The bad news is that her debut at the Hellfire Gala didn't go exactly as planned, and now all of mutantkind is being hunted worldwide! Plunged into a world of hate and fear, Kamala has a secret mission to pull off for the X-Men! Can an undercover Kamala infiltrate Orchis itself even as she struggles to acclimate to this new part of her identity? Collecting MS. MARVEL: THE NEW MUTANT #1-4, plus Kamala's first full appearance from ALL-NEW MARVEL NOW! POINT ONE #1.